Content validity and psychometric properties of the Nomination Scale for Identifying Football Talent (NSIFT): Application to coaches, parents and players - Prieto-Ayuso, A.; Pastor-Vicedo, J. C.; Contreras-Jordan, O. (Sports, 2016)
The identification of football talent is a critical issue both for clubs and the families of players. However, despite its importance in a sporting, economic and social sense, there appears to be a lack of instruments that can reliably measure talent performance. The aim of this study was to design and validate the Nomination Scale for Identifying Football Talent (NSIFT), with the aim of optimising the processes for identifying said talent. The scale was first validated through expert judgment, and then statistically, by means of an exploratory factor analysis (EFA), confirmatory factor analysis (CFA), internal reliability and convergent validity. The results reveal the presence of three factors in the scale`s factor matrix, with these results being confirmed by the CFA. The scale revealed suitable internal reliability and homogeneity indices. Convergent validity showed that it is teammates who are best able to identify football talent, followed by coaches and parents. It can be concluded that the NSIFT is suitable for use in the football world. Future studies should seek to confirm these results in different contexts by means of further CFAs.